Systematic revision and morphological phylogenetic analysis of Anchylorhynchus Schoenherr, 1836 (Coleoptera, Curculionidae: Derelomini) - de Medeiros, Bruno A. S.; Vanin, Sergio A. (Zootaxa, 2020)
Anchylorhynchus Schoenherr is a genus of palm-associated weevils currently including 22 described species in the Neotropics. These weevils engage in brood pollination interactions with species in at least four genera of palms (Arecaceae), representing an emerging system for the study of mutualisms. Here we revise the taxonomy of Anchylorhynchus and propose the first phylogenetic hypothesis for the group, based on morphology. Anchylorhynchus chrysomeloides sp. nov., Anchylorhynchus goiano sp. nov., Anchylorhynchus imitator sp. nov., Anchylorhynchus latipes sp. nov., Anchylorhynchus multisquamis sp. nov. and Anchylorhynchus rectus sp. nov. are described, Anchylorhynchus gottsbergerorum Vanin is a new junior subjective synonym of Anchylorhynchus bicarinatus O’Brien, and Anchylorhynchus eriospathae Bondar and Anchylorhynchus pictipennis Hustache are new junior subjective synonyms of Anchylorhynchus tremolerasi Hustache, resulting in 25 valid species for the genus. We provide genus and species descriptions with a new dichotomous key to the species and updated information on geography and host associations based on museum records and extensive new collections. We also produce a new morphological matrix with 113 characters, 11 of them based on measurements while accounting for allometry, correlation and power to delimit groups. The software pipeline to produce these characters was encoded in a graphical user interface named DiscretzR, made available here. Analysis of this matrix under parsimony and Bayesian inference resulted in strong support for the monophyly of Anchylorhynchus, but weaker support for most clades within the genus. Reconstruction of the host plant associations indicates that the common ancestor of Anchylorhynchus visited flowers of Syagrus Mart., with later transitions to other genera restricted to one of the major clades of Anchylorhynchus. This taxonomic revision with the first phylogeny for the group provides a foundation for future evolutionary studies in the genus.